A positive feedback loop mediated by CsERF31 initiates female cucumber flower development. Issue 2 (21st March 2021) - Pan, Jian; Wen, Haifan; Chen, Guanqun; Lin, Wen-Hui; Du, Hui; Chen, Yue; Zhang, Leyu; Lian, Hongli; Wang, Gang; Cai, Run; Pan, Junsong
Abstract: Sex determination is a crucially important developmental event that is pervasive throughout nature and enhances the adaptation of species. Among plants, cucumber ( Cucumis sativus L.) can generate both unisexual and bisexual flowers, and the sex type is mainly controlled by several 1-aminocyclopropane-1-carboxylic acid synthases ( CsACSs ). However, the regulatory mechanism of these synthases remains elusive. Here, we used gene expression analysis, protein–DNA interaction assays, and transgenic plants to study the function of a gynoecium-specific gene, ETHYLENE RESPONSE FACTOR31 ( CsERF31 ), in female flower differentiation. We found that in a predetermined female flower, ethylene signaling activates CsERF31 by CsEIN3, and then CsERF31 stimulates CsACS2, which triggers a positive feedback loop to ensure female rather than bisexual flower development. A similar interplay is functionally conserved in melon ( Cucumis melo L.). Knockdown of CsERF31 by RNAi causes defective bisexual flowers to replace female flowers. Ectopic expression of CsERF31 suppresses stamen development and promotes pistil development in male flowers, demonstrating that CsERF31 functions as a sex switch. Taken together, our data confirm that CsERF31 represents the molecular link between female–male determination and female–bisexual determination, and provide mechanistic insight into how ethylene promotes female flowers, rather than bisexual flowers, in cucumber sex determination. Abstract : A key regulator promotes female flower development by triggering a positive feedback loop during cucumber sex determination.